2016
DOI: 10.1186/s40709-016-0056-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation changes and TE activity induced in tissue cultures of barley (Hordeum vulgare L.)

Abstract: BackgroundIn vitro plant regeneration via androgenesis or somatic embryogenesis is capable of inducing (epi)mutations that may affect sexual progenies. While epimutations are associated with DNA methylation, mutations could be due to the movement of transposons. The common notion is that both processes are linked. It is being assumed that demethylation activates transposable elements (TEs). Analysis of methylation changes and their relation with TEs activation in tissue cultures requires uniquely derived donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 72 publications
(102 reference statements)
2
46
0
1
Order By: Relevance
“…One of the hypotheses of tissue culture-induced variation considers that sequence changes may be due to DNA demethylation and activation of mobile elements (Azman et al 2014;Orłowska et al 2016;Xu et al 2004). Our data indicate that DNA methylation/demethylation in barley affects symmetric sites and depends on the trial.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…One of the hypotheses of tissue culture-induced variation considers that sequence changes may be due to DNA demethylation and activation of mobile elements (Azman et al 2014;Orłowska et al 2016;Xu et al 2004). Our data indicate that DNA methylation/demethylation in barley affects symmetric sites and depends on the trial.…”
Section: Discussionmentioning
confidence: 58%
“…It is assumed that variation induced in regenerants may be partly inherited by generative progeny (Han et al 2018). Thus, regenerants subjected to generative cycle(s) should produce more uniform plants than regenerants (Machczyńska et al 2014b(Machczyńska et al , 2015Orłowska et al 2016Orłowska et al , 2020. Our recent studies demonstrated that, depending on the species and the number of generative cycles, the genome stabilisation level may vary (Machczyńska et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations